Supplementation of Aspergillus oryzae Culture Improved the Feed Dry Matter Digestibility and the Energy Supply of Total Volatile Fatty Acid Concentrations in the Rumen of Hu Sheep - Guo, Long; Zhang, Duihong; Du, Ruifang; Li, Fadi; Li, Fei; Ran, Tao (Frontiers in Nutrition, 2022)
The objective of the present study was to investigate the effects of feeding different amounts of Aspergillus oryzae culture (AOC) on the degradation rate of various feeds for 24 h, rumen fermentation parameters, microbial community, and blood cell composition of Hu sheep. Sixteen castrated and fattening adult Hu sheep with permanent rumen fistula were randomly divided into four groups (4 sheep per group) based on body weight (64.62 ± 5.83 kg). The experiment was repeated for two periods to ensure 8 replicates for each treatment, and each period consisted of 28 days, including a 7-d of transition, a 14-d of pre-feeding, and a 7-d of sample collection. The control group (CON) received a basal diet without AOC, and the other groups were fed basal diet supplemented with 10 g/d, 20 g/d, and 40 g/d AOC, respectively, every day before the morning feeding. Supplementation with 20 g/d and 40 g/d AOC significantly increased (P < 0.05) the total volatile fatty acids (TVFAs) content, the molar ratio of butyric acid, and the 24 h dry matter (DM) degradation rate of alfalfa hay and corn straw. When fed 40 g/d AOC, the DM degradation rate of corn germ meal and the relative abundance of Kiritimatiellaeota were significantly increased (P < 0.05), but the ratio of acetic acid to propionic acid (A/P) was significantly reduced (P = 0.04). In conclusion, supplementation with AOC for Hu sheep could improve feed DM digestibility and increase the energy supply of TVFAs concentration in the rumen. Based on the feed conditions of the present study, supplementation 40 g/d of AOC could increase the production efficiency of sheep while higher level have to further investigate.